Manifesta 7 : Index. - Manifesta Trentino South Tyrol 2008; Budak, Adam; Franke, Anselm; Grujthuijsen, Krist; Maier, Tobi; Peleg, Hila; Raqs Media Collective (Milano : Silvana Editoriale, 2008)
Adjaye, David ; Ahriman, Nader ; Airswap ; Aksamija, Azra ; Alterazioni Video ; Thereza, Maria ; Alves, Jimmie ; Taussig, Durham ; Taussig, Michael ; Amin, Shahid ; Antonioni, Michelangelo ; Asdam, Knut ; et al.
European Biennial of Contemporary Art, Trentino South Tyrol, 19 July - 2 November 2008
Index gathers short introductions to the works of more than 180 participants in Manifesta 7.
kunstcatalogus